LITERATURE REVIEW: JARAK DISTRIBUSI TERHADAP SISA KLOR DAN COLIFORM PADA AIR PDAM - Andryade Kurniawan; Akas Yekti Pulih Asih; Edza Aria Wikurendra (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The increase in population causes the need for clean water especially drinking water also increase. The distance that water in the pipeline travels to reach the customer will affect the quality of the water due to the possibility of contamination during the distribution process. The right remaining chlorine is one important aspect to ensure that water reache consumer with good quality, residual chlorine will have a direct impact on the content of coliform bacteria in water. The purpose of this study was to explain the distribution distance factor to the residual level of chlorine and coliform bacteria in PDAM water networks. This literature review uses the traditional literature review method, using the google scholar database. The keywords used are distance, residual chlorine, and coliform bacteria in PDAM water with a publication time span from 2010 to 2019. There are 11 articles that match the search process. Based on the results of the articles collected, it was found that the farther the distribution distance, the lower the residual chlorine content. The remaining chlorine content in the water keeps the water from leaching. The decreasing levels of residual chlorine in the water causes an increase in coliform bacteria. The distribution distance factor affects the residual chlorine, then affects the presence of coliform bacteria.